KISAH NABI YUSUF AS DALAM AL-QUR’AN - Hasiah, Hasiah (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2017)
The story of prophet Yusuf as is very beautiful story is comprehensively in a coherent story of prophet Yusuf since young to adulthood, from a human body to be a prophet, of acommoder to become a goverment official. The passage of time in the course of the story of prophet Yusuf. That so long is certainly filled with the turmoil of conflict and problems that are very diversi. So that these facts are not enough in the analysis alone. But it took the deepening of the language in order to understand the philosophical visible message contained there in.